2019
DOI: 10.1002/joc.6405
|View full text |Cite
|
Sign up to set email alerts
|

Recent rainfall trend over Sri Lanka (1987–2017)

Abstract: Rainfall trend analysis provides useful information for effective planning, and management of water resources, and gives an insight into climate change of a region. This study investigates trends in annual and seasonal rainfall over Sri Lanka using an Innovative Trend Analysis (ITA) and Mann–Kendall (MK) test with Sen's slope estimator. The MK test showed increasing trends in annual rainfall at 24 stations (65%) with five stations showing significant increasing trend. Annual rainfall at 13 locations (35%) show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 45 publications
3
32
1
Order By: Relevance
“…However, during Yala season, most parts of the country are getting dryer except far north and southwestern part. A similar trend was observed for the rainfall trend analysis for Yala and Maha season during the 1987-2017 period using MK test [35].…”
Section: Trend Analysis Of Spi For Rainfall Stationssupporting
confidence: 81%
See 2 more Smart Citations
“…However, during Yala season, most parts of the country are getting dryer except far north and southwestern part. A similar trend was observed for the rainfall trend analysis for Yala and Maha season during the 1987-2017 period using MK test [35].…”
Section: Trend Analysis Of Spi For Rainfall Stationssupporting
confidence: 81%
“…Most of these stations showing wetting tendencies are located in dry zone of the country except Chesterford, Geekiyanakanda, and Matale. Nisansala et al [35] analyzing the rainfall trend at 37 stations during the recent 31 years (1987-2017) showed an increasing annual rainfall trend over the country and further they showed a significant increase at four stations located in the dry zone, but only one station in the wet zone.…”
Section: Trend Analysis Of Spi For Rainfall Stationsmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, some studies have shown that urban temperature is rising in Sri Lanka [20]. Analysis of rainfall trends has become a research field that has attracted great interest and enthusiasm in recent times [21]. However, as the global or regional scale declines to the national or sub-national level, further localized variations can be observed [22].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, a large number of studies on rainfall trends in Sri Lanka have been conducted over the past three decades and identified different localized variabilities in the country [21,[38][39][40][41][42]. A recent study [21] showed that the eastern, southeastern, northern, and north-central parts of Sri Lanka have been experiencing an increase in rainfall over the past 31 years (1987-2017), and that there has been a decrease in the trend of rainfall in the western, northwestern, and central parts of the country.…”
Section: Introductionmentioning
confidence: 99%